Real-World Observational Review of Andexanet Alfa Prescribing and Utilization Outcomes at a Community Teaching Hospital. (2nd April 2021) - Sobolewski, Kristine A.; Brophy, Alison; Choi, Seohyun (Claudia); Opsha, Yekaterina
Abstract : Objectives: Andexanet alfa is the first approved antidote in the management of life-threatening bleeds in patients treated with Xa inhibitors. The ANNEXA-4 study was successful in reducing factor Xa levels during time of administration but lacked correlation to improved patient outcomes. Given its novel mechanism of action, U.S. boxed warning, cost of up to 58, 000 per dose, and limited efficacy data compared with standard of care, hospitals are faced with a dilemma with its addition to formulary and process for ensuring optimized use. The objective of this study was to evaluate adherence to institution restriction criteria and the clinical outcomes of treatment for patients for whom andexanet alfa is requested. Design: Retrospective cohort study of andexanet alfa requests within a 12-month time period. Setting: A 600-bed community teaching hospital. Patients: Patients whom pharmacists received request for dispensing andexanet alfa. Interventions: None. MEASUREMENTS AND MAIN RESULTS: Quality outcomes reviewed compliance to restriction criteria. Clinical outcomes evaluated use of adjunctive blood products, ICU length of stay, hospital length of stay, and hospital mortality. Safety outcomes evaluated incidence of thrombotic events. Andexanet alfa was requested for 16 patients from November 2018 to November 2019. It was administered in nine patients, with compliance to restriction criteria of 66.6%, average ICU length of stay 5.6 days, hospital length of stay 8.6 days, hospital mortality in 44.4%, and thrombotic events in 33.3%. Orders were rejected in seven patients with compliance to restriction criteria of 100%, ICU length of stay 3.2 days, hospital length of stay 5.5 days, hospital mortality in 14%, and thrombotic events in 14%. Conclusions: A greater rate of adverse effects and mortality was identified with the use of andexanet alfa compared with clinical trials. This is potentially due to its use in a more severely ill patient population and lack of adherence to restriction criteria.